SPREE estimation of the number of disabled people in terms of economic activity - Szymkowiak, Marcin; Wilak, Kamil (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
The creation of equal opportunities in the labour market for people with disability remains a challenge in many countries around the world. The impact of disability, especially when it comes to work opportunities for disabled people, cannot be properly understood without access to the relevant statistics. Information about working-age disabled people is crucial in the development of labour market policy. Such information should be available not only at the national level but also at lower levels of spatial aggregation. The main aim of this article is to propose a way of producing reliable estimates of key labour market indicators (economic activity rate, employment rate and unemployment rate) for working-age disabled people in Poland at the province level. The authors apply SPREE estimation and use data from the Labour Force Survey 2011–2019 (LFS) and the 2011 Census to produce estimates characterized by better precision and stability over time than what can be achieved by applying direct estimation. While the scale of changes in the labour market situation of working-age disabled people was found to be similar to trends observed in the whole working-age population, there are differences in spatial patterns associated with these two groups.